Urgensi Literasi Dokumen Teknis dalam Pendidikan Bahasa Indonesia bagi Mahasiswa Teknik Sipil: The Urgency of Technical Document Literacy in Indonesian Language Education for Civil Engineering Students - Djuwandi, Nayyara Kamila; Vitraloka, Gadis; Davrie, Atilla Muhammad; Kuncoro, Muhammad Rizaldi; Prabowo, Dimas Seto; Rizkyanfi, Mochamad Whilky (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
Technical document literacy is a critical competence for Civil Engineering students, yet it has not been optimally integrated into Indonesian language courses at the university level, creating a gap with professional demands in the Construction 4.0 era. This study aims to evaluate the relevance of Indonesian language instruction to the technical communication competence required by IABEE Criterion 1.3.f in Civil Engineering programs. A descriptive qualitative approach was employed through a comparative analysis of Indonesian language Semester Learning Plans from five Civil Engineering programs at public universities. The findings indicate that most RPS remain oriented toward generic academic writing and do not position technical documents such as construction contracts, Cost Budget Plans, Work Plans and Specifications (RKS), and material specifications as primary learning objects, leaving the actual technical document literacy needs of the construction industry unaddressed. The study concludes that recontextualizing Indonesian language teaching through a Language for Specific Purposes (LSP) approach that integrates technical documents and project‑based collaborative tasks is a promising strategy to develop professional literacy aligned with accreditation standards and industry needs.